The influence of environmental factors on daily milk yield and fat and protein content in Istrian sheep - Marija Špehar; Josip Vrdoljak; Vesna Pavić; Boro Mioč; Zdravko Barać (Mljekarstvo, 2012)
The objective of this study was to analyse the effect of stage of lactation, parity, litter size, and lambing season on daily milk production and fat and protein content in Istrian sheep. Data included9.533 test-day records of 2.024 ewes for the period from October 2005 to May 2009. Daily milk yield and fat and protein content were determined during monthly milking controls using AT4 method. The stage of lactation, described by Wilmink lactation curve, had significant effect (P<0.001) on all studied milk traits of Istrian sheep. The peak of daily milk production was achieved between the 20th and 30th day of lactation and gradually decreased towards the end of lactation. Lactation curves for fat and protein content had opposite shape compared to the daily milk yield lactation curve. Parity affected (P<0.05) the daily milk yield and protein content. Daily milk yield and protein content were the lowest in the first and the highest in the third parity. Statistically significant influence of litter size (P<0.05) was determined for daily milk yield and fat content. A higher daily milk yield and lower fat content was observed in ewes lambing twins compared to ewes lambing singles. Differences in daily milk yield and contents were observed for the lambing season effect (P<0.001). Istrian ewes lambed in December and November (first lambing season) had the highest daily milk production, while the lowest daily milk yield had ewes lambed in February.